A Full Aperture Backscattering Light Diagnostic System Installed on the Shenguang-Ⅲ Prototype Laser Facility - 徐涛 梅雨 魏惠月 彭晓世 王峰 杨冬 刘慎业 闫亚东 (Plasma science & technology, 2014)
A full aperture backscattering light diagnostic system （FABLDS） implemented on the Shen Guang-Ⅲ Prototype Laser Facility is described in the paper. FABLDS measures both stimulated brillouin scattering （SBS） and stimulated Raman scattering （SRS） with a series of optical detectors. Energy sensors record the integrated energy, and streak cameras coupled with spectrometers measure the temporal spectrum of the backscattering light. This paper provides an overview of the FABLDS and detailed descriptions of the optical path. Special components, including off-axis parabolic mirror, spatial filter and optical light filters, are incorporated along the beam path for purifying the scattering light. Several hohlraum targets were employed, including C5H12 gas-filled targets and empty targets in the experiments. Results presented in the paper indicate that the fraction of backscatter light has been obviously shrinked when the laser is smoothed by continuous phase plates （CPP）.